THE ENHANCEMENT OF REPORTING OBSERVATION RESULT SKILL AND GIVING REASON SKILL ON THE MATERIAL OF SOLUBILITY AND SOLUBILITY PRODUCT BY ADVANCE ORGANIZER LEARNING MODEL - dena marista; noor fadiawati; nina kadaritna (Universitas Lampung, 2012)
The aim of this research was to describe the effectiveness of advance organizer learning model to enhance the skill of reporting observation result and giving reason skill on the material of solubility and solubility product. The subject in this research were students XI grade of Science 3 SMA N 7 Bandarlampung, Academic Year 2011/2012. This research used a pre-experimental method with One Group Pretest-Posttest Design. The effectiveness of advance organizer learning model was measured by the N-gain mean. Based on the results of this research, the average of N-gain value for reporting observation result skill is 0,67 and the average of N-gain value for giving reason skill is 0,54. This shows that (1) a model of advance organizer is effective to enhance the skill of reporting observation result in the medium category (2) a model of advance organizeris effective to enhance the skill of giving reason in the medium category.Keywords: Advance Organizer learning model, the observation result report skill and the give reason skill